Elucidation of stoichiometric efficiency, radical generation and transformation pathway during catalytic oxidation of sulfamethoxazole via peroxymonosulfate activation - Bao, Yueping (2020)
In this work, nano-bimetallic Co/Fe oxides with different stoichiometric Co/Fe ratios were prepared using a novel one-step solution combustion method. The nano-bimetallic Co/Fe oxides were used for sulfamethoxazole (SMX) degradation via peroxymonosulfate (PMS) activation. The stoichiometric efficiencies of the as-prepared nano-bimetallic catalysts were calculated and compared for the first time. The radical generation was identified by electron paramagnetic resonance (EPR) as well as chemical quenching experiments, in which different scavengers were used and compared. The catalytic PMS activation mechanism in the presence of catalyst was examined by Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The results showed that besides SO4•- and •OH, •OOH was also detected in the PMS/CoFeO2.5 system. Meanwhile, in addition to the previously proposed radical oxidation pathway, the results showed that SMX degradation also involved a non-radical oxidation, which could be verified by the degradation experiment without catalyst as well as the detection of 1O2. In the PMS activation process, cobalt functioned as the active site on CoFeO2.5 while Fe oxide functioned as the adsorption site. The electron transfer mechanism was proposed based on the XPS and metal leaching results. Additionally, via the detection of transformation products, different SMX transformation pathways involving nitration, hydroxylation and hydrolysis in the PMS/CoFeO2.5 system were proposed.